PENINGKATAN AKTIVITAS DAN KERJA SAMA DALAM KULIAH DRAMA PADA MAHASISWA SEMESTER III PENDIDIKAN BAHASA DAN SASTRA INDONESIA PBS FKIP UNIVERSITAS JAMBI - D., Yusra (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2014)
This  article  presents  the  results  of  research  about  Increased  Activity  and Cooperation  of  Student  in  Drama  Class  of  The  third  Semester  of  Pendidikan Bahasa dan Sastra Indonesia PBS FKIP UNJA.  Methods  to  increase the activityand  cooperation  of  students,  in this study,  is a  participatory method  and the  two stay two stray  method.  The results showed  that  through  the application of  these methods, activities and cooperation in student learning can be improved.Keywords:  activity  and  coorperation  of  student,  participatory  method,  the  two stay two stray method